2021
DOI: 10.3390/cancers13133375
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-Fetoprotein- and CD40Ligand-Expressing Dendritic Cells for Immunotherapy of Hepatocellular Carcinoma

Abstract: Dendritic cells (DC) as professional antigen presenting cells are able to prime T-cells against the tumor-associated antigen α-fetoprotein (AFP) for immunotherapy of hepatocellular carcinoma (HCC). However, a strong immunosuppressive tumor environment limits their efficacy in patients. The co-stimulation with CD40Ligand (CD40L) is critical in the maturation of DC and T-cell priming. In this study, the impact of intratumoral (i.t.) CD40L-expressing DC to improve vaccination with murine (m)AFP-transduced DC (Ad-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…Recently, the combination of DC vaccine with ICIs has shown promising results 145,146. In preestablished in vivo subcutaneous and orthotopic HCCs, AFP‐DCs alone induced a significant reduction and a slight delay of tumor growth, whereas combination of AFP‐DCs and CD40L‐expressing DCs had a synergistic effect associated with an enhanced Th1‐cytokine level, tumor infiltration of cytotoxic T lymphocytes, and tumor apoptosis 147. Also, an orthotopic HCC mouse model treated with a DC vaccine in combination with a PD‐1 inhibitor showed longer overall survival than monotherapy and led to a greater reduction of tumor volume by inducing apoptosis 145.…”
Section: Dcs Get T Cells Rollingmentioning
confidence: 99%
“…Recently, the combination of DC vaccine with ICIs has shown promising results 145,146. In preestablished in vivo subcutaneous and orthotopic HCCs, AFP‐DCs alone induced a significant reduction and a slight delay of tumor growth, whereas combination of AFP‐DCs and CD40L‐expressing DCs had a synergistic effect associated with an enhanced Th1‐cytokine level, tumor infiltration of cytotoxic T lymphocytes, and tumor apoptosis 147. Also, an orthotopic HCC mouse model treated with a DC vaccine in combination with a PD‐1 inhibitor showed longer overall survival than monotherapy and led to a greater reduction of tumor volume by inducing apoptosis 145.…”
Section: Dcs Get T Cells Rollingmentioning
confidence: 99%
“…The combination of the AFP-DCs vaccine with CD40 ligand-DCs vaccine has shown synergistic results. It changes the TME, enhances the tumor infiltration of cytotoxic T lymphocytes and DCs, and upregulates Th1-derived cytokines, leading to tumor apoptosis and regression ( 92 , 93 ). A phase I/II trial measuring immunization in HCC patients found that AFP-DCs vaccine can produce AFP-specific T cell responses with increasing IFN-γ in the environment of high oncofetal antigen ( 86 ).…”
Section: The Role Of Afp In the Diagnosis And Treatment Of Hccmentioning
confidence: 99%
“…Many studies on novel DC vaccines have recently emerged, laying a solid theoretical foundation for the development of effective DC vaccines in the treatment of HCC. CD40L on activated CD4 + Th cells can communicate with CD40 on DCs to promote the secretion of Th1 cytokines by DCs, and the CD40L-DCs were confirmed to improve the anti-tumor activity of the AFP-DC vaccine in an orthotopic HCC mouse model, and the combination of them could significantly suppress tumor progression, accompanied by a robust Th1-shift in the TME and increased tumor cell apoptosis [ 227 ]. Furthermore, CSC/DC fusion cells could promote CTL accumulation in HCC and enhance anti-tumor immunity in animal experiments [ 228 ].…”
Section: Hcc Immunotherapiesmentioning
confidence: 99%